Perencanaan Bisnis Berbasis Potensi Desa: BUMDes Ngudi Luhur, Desa Sambirata, Kecamatan Cilongok, Kabupaten Banyumas - Ira Hapsari; Erna Handayani; Nur Isna Inayati; Mukti Agung Wibowo; Mukhlis Prasetyo Aji; Wanda Nugroho Yanuarto; M. Zaeni Lathif (Prisani Cendekia, 2023)
Abundant village potential that has not been developed into business potential that can contribute to village development and the welfare of village communities. The abundant village potential in Sambirata Village, Cilongok District, Banyumas Regency, Central Java, includes abundant natural resources and human resource potential. For development to become a profitable business, it needs to be mapped out in depth in a business proposal. Therefore, one of the important roles of tertiary institutions is to provide continuous assistance and collaboration to realize independent village development. One way is by assisting in the preparation of business proposals and mapping business potential in the village.